Attenuated Replication-Competent Herpes Simplex Virus Expressing an ECM-Modifying Transgene Hyaluronan Synthase 2 of Naked Mole Rat in Oncolytic Gene Therapy - Palomäki Jussi; Kalke Kiira; Orpana Julius; Lund Liisa; Frejborg Fanny; Paavilainen Henrik; Järveläinen Hannu; Hukkanen Veijo (MDPI, 2025)
Herpes simplex virus (HSV) has proven successful in treating human cancer. Since the approval of talimogene laherparepvec (T-VEC) in 2015, HSV has been thoroughly researched to discover novel mechanisms to combat cancer and treat other diseases. Another HSV-based drug, beremagene geperpavec (B-VEC), received approval in 2023 to treat the rare genetic disease dystrophic epidermolysis bullosa, and was also the first clinically approved HSV vector carrying an extracellular matrix (ECM)-modifying transgene. The ECM is a network of macromolecules surrounding cells, which provides support and regulates cell growth and differentiation, the disruption of which is common in cancer. The naked mole rat (NMR) has a thick ECM and a unique mutation in the hyaluronan synthase 2 (HAS2) gene, which has been linked to the high cancer resistance of the species. To study the effect of this mutation in human cancer, we have developed an attenuated, replication-competent HSV vector expressing the NMR-HAS2 gene. The viral replication, transgene expression and cytotoxic effect of the novel vector was studied in glioma cells. Our results show that an attenuated, replication-competent HSV vector expressing a foreign ECM-modifying transgene, namely HAS2, provides an effective tool to study and combat cancer in humans.